2018
DOI: 10.1038/gim.2017.134
|View full text |Cite|
|
Sign up to set email alerts
|

Reproductive genetic carrier screening for cystic fibrosis, fragile X syndrome, and spinal muscular atrophy in Australia: outcomes of 12,000 tests

Abstract: PurposeTo describe our experience of offering simultaneous genetic carrier screening for cystic fibrosis (CF), fragile X syndrome (FXS), and spinal muscular atrophy (SMA).MethodsCarrier screening is offered through general practice, obstetrics, fertility, and genetics settings before or in early pregnancy. Carriers are offered genetic counseling with prenatal/preimplantation genetic diagnosis available to those at increased risk.ResultsScreening of 12,000 individuals revealed 610 carriers (5.08%; 1 in 20): 342… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 27 publications
7
96
0
1
Order By: Relevance
“…Our previous study of carrier rates in 346 790 patients showed that an ECS panel was expected to identify more pregnancies at risk for serious conditions than ethnic-based panels spanning far fewer genes (4 ), and the American College of Obstetricians and Gynecologists recently recognized ECS as an acceptable strategy for preconception and prenatal carrier screening (5 ). To the extent that these guidelines increase ECS usage, they will have a large clinical impact because it has recently been shown in clinical-utility studies that approximately 80% of couples found to be at risk for severe conditions pursue alternative reproductive options (6,7 ).…”
Section: © 2018 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Our previous study of carrier rates in 346 790 patients showed that an ECS panel was expected to identify more pregnancies at risk for serious conditions than ethnic-based panels spanning far fewer genes (4 ), and the American College of Obstetricians and Gynecologists recently recognized ECS as an acceptable strategy for preconception and prenatal carrier screening (5 ). To the extent that these guidelines increase ECS usage, they will have a large clinical impact because it has recently been shown in clinical-utility studies that approximately 80% of couples found to be at risk for severe conditions pursue alternative reproductive options (6,7 ).…”
Section: © 2018 American Association For Clinical Chemistrymentioning
confidence: 99%
“…In this situation, the couple have a 1-in-4 risk of an affected child in each pregnancy. Since carriers of recessive diseases are usually unaffected, children with recessive diseases are most often born into families with no history of the disease 1. The risk of having a child with these severe recessive diseases is higher than2 or equal1 to the birth prevalence of children with Down syndrome 3.…”
Section: Introductionmentioning
confidence: 99%
“…Since carriers of recessive diseases are usually unaffected, children with recessive diseases are most often born into families with no history of the disease 1. The risk of having a child with these severe recessive diseases is higher than2 or equal1 to the birth prevalence of children with Down syndrome 3. Genetic disease is responsible for a significant proportion of infant morbidity and mortality4 and the burden of genetic disease on patients, families and society in terms of suffering and cost is large.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, medical progress is increasing the probability of survival for children with severe genetic disorders; on the other, genetic screenings are offering a way to reduce the birth of newborns with relatively common severe disorders like cystic fibrosis, SMA, and thalassemia[51,52]. It may be difficult to find the correct direction between full fruition of life and the maintenance of some vital function with unbearable sufferance.…”
Section: Resultsmentioning
confidence: 99%